Hubungan Aliran Kas Bebas Dan Kebijakan Dividen Set Kesempatan Investasi Sebagai Variabel Moderasi - Ferry Hendro Basuki (SOSIALITA, 2011)
The objectives of this study are to emprically examine the association between free cash flow and dividend policy, and test the influence investment opportunity set as moderating variable to the correlation. Variable used in this research is investment opportunity set measured hence proxy based on the price that is market to book value of equty (MBVE), free cash flow, and dividend policy. This variable are later then analysed by using method of pooled regression that is model the linear regresi by adding cross-product term. As much 89 company which have publik at Jakarta Stock Exchange (JSX) except mining company, bank, insurance, sekuritas, real estate, credit agent, hotel and travel which used as sampel research. Test the assumption classical indication there are trouble heteroskedastisitas, after done by remedial hence the rest of 216 from 445 perception weared to test the alternative hypothesizing one and alternative hypothesizing two. The empiric result obtained depict that free cash flow individually correlate the negativity and dont significan with the dividend policy without including moderasi set the invesment opportunity, and so do when testing free cash flow relation with the dividend policy by including to invesment opportunity set as its moderating variable result depict the negative relation and dont significan. this finding Impirik explain that invesment opportunity set unable to influence the free cash flow relation and dividend policy, even so there relation is very small.